Simulation of micro aggregate breakage in turbulent flows by the cumulant lattice Boltzmann method. (25th November 2016) - Far, Ehsan Kian; Geier, Martin; Kutscher, Konstantin; Krafczyk, Manfred
Highlights: Two-scale model to describe the mechanical dispersion of micro-aggregates. High-resolution implicit LES computation by the Cumulant LBM. Study of the effect of particles' fractal dimension on breakage probability. Abstract: The production of nano-particles from larger aggregates is an important industrial process, especially for life-science products. A micro-machined disperser is studied numerically by the cumulant lattice Boltzmann method. The aggregates are modeled as tracer particles with mass and drag coefficient. They record the history of the experienced stresses and the relative velocity of aggregates with respect to the fluid. The tracer particles are implemented in a massively parallel multi-resolution lattice Boltzmann framework. In this paper, the effect of fractal dimension and the number of primary particles on the breakage of aggregates due to the relative velocities of the particles with respect to the surrounding fluid are investigated. It is found that aggregates with realistic geometry (fractal number 1.85) usually have Stokes numbers smaller than one such that the load on these aggregates is dominated by the strain rate in the surrounding fluid. This is in contrast to spherical particles (fractal number 3) that have larger Stokes numbers exceeding one such that the load from their relative velocity with respect to the surrounding fluid is not negligible.